Physicochemical Characteristics of Smoked Dumbo Catfish Sausage Due to Differences in Liquid Smoke Concentration and Immersing Duration - Ernawati, .; Roisatul, Ainiyah; Matheus, Nugroho; Senja, Ikerismawati; Illiyatus, Sholiha; Nikmatul, Izah (INTI International University, 2025)
Dumbo catfish (Clarias gariepinus) is currently in high demand among consumers. Product diversification is essential to increase its market value and competitiveness. One of the processing methods for dumbo catfish is smoked sausage production using liquid smoke. Smoked sausage is reported to contain antioxidants derived from smoke components. This study aimed to determine the physicochemical characteristics of smoked dumbo catfish sausage processed with liquid smoke. The research employed a factorial randomized block design with two treatment factors. The first factor was liquid smoke concentration (15%, 20%, and 25%), while the second factor was immersion time (15, 30, and 45 minutes). The parameters analyzed included moisture, fat, protein, phenol, and total acid content. The variation in liquid smoke concentration and immersion time significantly affected phenol and total acid content, while moisture, protein, and peroxide values were not significantly different. Moisture content ranged from 61.52% to 62.68%, protein content from 42.96% to 43.88%, phenol levels from 234.92 to 366.81 ppm (equivalent to 0.023–0.037%), and total acid content ranged from 5.72 to 7.25 mg/100 g. Overall, the analysis indicated that smoked dumbo catfish sausages produced with different combinations of liquid smoke concentration and immersion time still met the standards of SNI 01-3820-1995 on Fish Sausage and SNI 2725:2013 on Smoked Fish